International Equity Market Integration: An Analysis of the Islamic Capital Markets - Abdul Rahim, R.; Janor, H.; Yusof, M. Z.; Sapian, R. Z. (Universiti Sains Islam Malaysia, 2024)
This study intends to establish new evidence on the allegation that emerging markets tend to be partially integrated at the regional level but remain segmented from the world equity markets. This objective is achieved through investigating the integration between Malaysia and most important players in world equity markets, namely US, UK, Japan and Canada as well as Europe, emerging and developed market on a more regional and global platforms. In this study, Asia Pacific serves the role of Malaysian's regional market. But more importantly, this study could be the first of its kind to establish evidence on stock market integration from the new but highly progressive Islamic stock markets (ISM). This is done by utilizing the Dow Jones Islamic Market indices for the selected markets, from the most recent period of 1999:06 to 2007:06. The analysis of the structure of dynamic linkages among the selected Islamic stock markets utilizes the vector-autoregressive analysis (VAR). The results from the analyses lead to the following conclusions; (i) in general the dynamic interdependence between Malaysian ISM and the other major markets are still weak, (ii) there is a relatively stronger interdependence between ISM of Malaysia and the US than those between Malaysia and other markets including Japan, and (iii) there is some evidence suggesting stronger intra- than inter-regional integration based on the interdependencies between Malaysia and Asia Pacific and World Emerging markets. Overall, the findings imply a great prospect for Malaysian Islamic equity markets to be promoted as a viable investment vehicle for the advanced markets to improve their portfolio diversification.